Healthcare providers' and deaf patients' interpreting preferences for critical care and non-critical care: Video remote interpreting. Issue 2 (April 2020) - Yabe, Manako
Abstract: Background: While Video Remote Interpreting services provides prompt services for emergency care and is cheaper than in-person interpreting services, there have been several issues, such as poor connection and limited flexibility to maneuver. Objectives: This study proposes three research questions and four hypotheses to identify healthcare providers and deaf/hard of hearing (DHH) patients' preferences for VRI and in-person interpreting on critical care and non-critical care. Methods: The study utilizes a mixed methods design incorporating both an online survey and qualitative interviews. A total of 103 participants responded to the online survey. This included 36 healthcare providers who worked with limited English proficiency (LEP) patients, 26 healthcare providers who worked with DHH patients, and 41 DHH patients. Qualitative interviews were also conducted with eight healthcare providers and eight DHH patients to explore the online survey findings. Results: In the Part I study, healthcare providers ( n  = 62) included 16 males and 45 females; most professions were dentists, nurse practitioners, and students. DHH patients ( n  = 41) included 17 males and 22 females; most education was graduate or professional degrees. There was no statistical difference in their preference uses for critical care ( p  = 1.000), but there was a statistical difference for non-critical care ( p  = .035). In the Part II study, both healthcare providers and DHH patients preferred in-person interpreting for critical care to obtain effective communication, translation accuracy, and better treatment. Conclusions: Recommendation to improve VRI equipment and training with healthcare providers, hospital administrators, VRI companies, VRI interpreters, and DHH patients to improve healthcare communication.